PENGARUH BRAND CHARACTERISTIC, COMPANY CHARACTERISTIC DAN KEPERCAYAAN MEREK PADA LOYALITAS MEREK: Studi Pada Konsumen Jamu Tolak Angin Sidomuncul di Kota Yogyakartaâ, - , Prasojo Pribadi, S.Far.; , Prof. Dr. Basu Swastha Dh., MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Various researchers about brand have been done, however such loyalty problem in brand stills need to study exhaustively and comprehensive. Loyalty character is very importance where there tenacious confidence that loyalty has positive connection with profitability. This research aims to see influence of brand characteristic and company characteristic variable in brand loyalty with trust in a brand variable as mediation variable of consumer of Jamu Tolak Angin Sidomuncul at Yogyakarta city. This research is correlation research with instrument as questioner that filled by respondent that amount to 175 respondents. Design of taking manner sample non probability that used in this research is taking according to purposive, where respondent in this research is consumer that has loyalty towards brand of Jamu Tolak Angin Sidomuncul at Yogyakarta city. To test validity is used Principal Component Analysis (PCA) method and to test reliabilities by using Cronbachs âAlpha. After got valid result and reliable, then done hypothesis test uses simple regression and double regression. From test result if this hypothesis as a whole inferential that brand competence, trust in the company, and company reputation proved positive influential in trust in a brand, trust in a brand proved positive influential in brand loyalty. Brand characteristic and company characteristic direct positive influential in brand loyalty but influence that evoked preponderant when pass trust in brand before hand as variable that mediation a part relation brand characteristic and company characteristic variable with brand loyalty variable.